(untitled) (Eurasian Journal of Research, Development and Innovation, 2026)
This study examines sustainable hospitality and destination development in Dubai as a state-led model within an emerging economy. Using market projections, hotel inventory data, and academic literature, it analyzes how infrastructure investment, regulatory coordination, and sustainability integration support sector growth. Despite rapid supply expansion, high occupancy rates and projected market growth indicate structural resilience. The findings suggest that sustainability in Dubai is embedded within long-term economic diversification, though risks related to oversupply and environmental pressure persist